Laser-induced modifications of polyvinyl alcohol/starch blends. Issue 5 (3rd June 2021) - Sreekumar, P. A; Thomas, Selvin P.; Al-Harthi, Mamdouh A.; Gondal, M. A.; De, S. K.
ABSTRACT: Effects of laser irradiation on the thermal properties and morphological structure of starch, polyvinyl alcohol (PVA) and their blends were studied. Laser irradiation has an insignificant effect on the thermal behaviour of starch and PVA, but it causes an increase in crystallization and melting temperature ( T cry and Tm ) for blends as a function of irradiation time. Thermogravimetric analysis (TGA) further indicates breakdown of the intermolecular attractive forces on laser irradiation, causing a decrease in the blend homogeneity. Fourier infrared spectroscopic (FTIR) and scanning electron microscopic (SEM) studies corroborate the above findings.